Nazione ed economia politica nell’impero luso-brasiliano - Milena Fernandes de Oliveira è professoressa dell’Universidade Estadual de Campinas (Stato di São Paulo). La sua attività di ricerca è incentrata sull’analisi del rapporto tra l’idea di nazione e l’economia politica nel passaggio dal XVIII al XIX secolo. Si occupa di storia economica, principalmente dei secoli XVIII e XIX e in particolare dei processi di formazione del capitalismo. (Diacronie. Studi di Storia Contemporanea, 2014)
This paper examines the idea of nation during the Ancient Regime’s crisis in Portugal. The research’s foreword tries to understand how the nation was thought across the two sides of the Atlantic sea: from the late XVIII century Portugal to the American colonies, who began to consider themselves as an independent state, Brazil. The proposal is to compare this idea of nation to the modern forms of society interpretations, based on the market conception. The Portuguese case is particularly rich for his contradictions.